2012
DOI: 10.1097/01.pra.0000416016.37968.eb
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Facets of Personality in a Patient Sample of Hypersexual Women Compared with Hypersexual Men

Abstract: This study explored group differences among a treatment-seeking sample of hypersexual women (n = 31) and hypersexual men (n = 47) across facets of personality using the NEO-Personality Inventory-Revised and the Hyper sexual Behavior Inventory. A number of striking parallels emerged between the two groups, including similar levels of impulsivity, emotional dysregulation, and difficulties coping with stress. Hypersexual women, compared to men, exhibited higher levels of distrust toward others, lower levels of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 21 publications
2
32
1
4
Order By: Relevance
“…The HBI's three-factor, first-order model of hypersexuality has shown strong psychometric properties in terms of confirmatory factor analysis (CFA), high internal consistency, and high test-retest reliability (e.g., Klein, Rettenberger, Boom, & Briken, 2014;Reid et al, 2011;Yeagley et al, 2014). Moreover, the HBI has been demonstrated to have strong concurrent, criterion, discriminant, and clinical validity in previous studies (e.g., Montgomery-Graham, 2016;Reid, Dhuffar, Parhami, & Fong, 2012;Yeagley et al, 2014).…”
Section: Institute Of Psychology Elte Eötvös Loránd Universitymentioning
confidence: 99%
“…The HBI's three-factor, first-order model of hypersexuality has shown strong psychometric properties in terms of confirmatory factor analysis (CFA), high internal consistency, and high test-retest reliability (e.g., Klein, Rettenberger, Boom, & Briken, 2014;Reid et al, 2011;Yeagley et al, 2014). Moreover, the HBI has been demonstrated to have strong concurrent, criterion, discriminant, and clinical validity in previous studies (e.g., Montgomery-Graham, 2016;Reid, Dhuffar, Parhami, & Fong, 2012;Yeagley et al, 2014).…”
Section: Institute Of Psychology Elte Eötvös Loránd Universitymentioning
confidence: 99%
“…This finding is also in line with other reports of the association between excessive Internet gaming [58] or Internet gambling [19] and depression. Such associations suggest that excessive cybersex is at least partly a coping behavior that aims to regulate negative emotions [18,35,36,41,59]. This finding opens the debate, as has occurred for other Internet addictive-like behaviors, about an appropriate diagnostic framework [14] and adequate understanding of such an association [60].…”
Section: Discussionmentioning
confidence: 91%
“…Nonetheless, to date, the association between cybersex and impulsivity has also received little attention [18], and in those studies that have examined this association, mixed results were found. In some studies, lack of executive control [22,23] and impulsivity facets were associated with hypersexuality [41,42] or addictive cybersex [22,23]. In contrast, Wetterneck et al [28] did not find any differences on impulsivity measures between problematic and non-problematic pornography use.…”
Section: Introductionmentioning
confidence: 87%
“…En chicas, la probabilidad de manifestar problemas en el control de impulsos sexuales en las que puntuaban bajo en esta faceta es del 62% frente al 38% de las que puntúan alto, lo que se ajusta por completo a los trabajos que sugieren que las personas con menor amabilidad tienen mayor probabilidad de experimentar un comportamiento sexual compulsivo (Kastner & Sellbom, 2012;Reid, Dhuffar, et al, 2012). Sin embargo, en chicos el factor que incrementa el riesgo (60%) es precisamente puntuar alto en esta faceta.…”
Section: Modelos Predictivos Y Explicativos Del Cuadro Clínico De Csunclassified
“…La vía directa comprendería las dimensiones de apertura a la experiencia (relacionada positivamente con la CS) y de amabilidad y responsabilidad (relacionadas de forma negativa). A excepción de la de apertura (que en los escasos estudios realizados nunca había resultado ser un predictor significativo del nivel de CS) (Rettenberger et al, 2015), las otras dos dimensiones se han relacionado sistemáticamente con el control de impulsos sexuales a través de múltiples investigaciones (Kastner & Sellbom, 2012;Reid, Dhuffar, et al, 2012). La vía indirecta comprende las dimensiones de personalidad de neuroticismo y extraversión, que influirían sobre el nivel de CS potenciando tendencias psicopatológicas (ansiedad-estado y depresión) y facilitando la emergencia de distintos cuadros clínicos.…”
Section: Modelos Predictivos Y Explicativos Del Cuadro Clínico De Csunclassified